The sense of identity among adolescents. The qualitative research - Kłosowski, Marcin (Studia Psychologica: Theoria et praxis, 2019)
Adolescence is a period of physical and mental transformation from childhood to adulthood. One of the most important tasks at that time is forming the sense of identity. According to Erikson (1968) an identity crisis occurs during that stage and the most important question appears “who am I?” The problem of the content and the form of the sense of identity among adolescents aged 13–19 has been discussed in the article. Qualitative research was conducted with the original tool among students of gymnasium and high school (the research was completed before the liquidation of gymnasium in Poland). 188 students participated in the study (N = 188, gymnasium students n = 96, high school students n = 92, mean age = 16.20). As a result of the analyzes, it turned out that there are some differences in the content and form of statements between gymnasium and high school students. It can also be stated that adolescents differ not only in specific content, but also in the ability or disability to answer the question about the individual sense of identity.